THE ROLE OF WAITING FOR TUBANG WHO MIGRATES TO STUDY MUARA TENANG VILLAGE, SEMENDE DARAT TENGAH DISTRICT, MUARA ENIM REGENCY - Izawahi Izawahi; Dadang Hikmah Purnama; Yunindyawati (SOSIOEDUKASI, 2026)
This study aims to analyze the changes in the role of Tunggu Tubang in the Semende community, especially in the context of overseas, and examine these roles based on structural, normative, behavioral, interactional, and role expectation dimensions. The method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The informants in this study consist of Tunggu Tubang, family members, and traditional leaders (Meraje). The results of the study show that there has been a shift in the role of Tunggu Tubang from direct management of heritage in the village to indirect management through economic contributions and remote supervision. Nevertheless, the status and responsibilities of Tunggu Tubang remain inherent and recognized in the customary system. In the structural dimension, the role of Tunggu Tubang is in a collective system with the involvement of extended families and supervision of Meraje. In the normative dimension, the role is governed by customary values and norms that emphasize responsibility and sustainability of inheritance. In the behavioral and interactional dimensions, the role of Tunggu Tubang is manifested through management, communication, and deliberation with families and traditional leaders. Meanwhile, in the dimension of expectation, the community has expectations that Tunggu Tubang will be able to carry out its role optimally in order to maintain family harmony. This study concludes that the Tunggu Tubang system is adaptive to social changes, especially due to overseas, without eliminating the basic values that are the foundation of customs. These changes are actually a form of strategy in maintaining the sustainability of the customary system in the midst of the dynamics of modern life.